Предмет: Алгебра, автор: EysiMilz

x³ + 8
27 + a³
1 + m^6
p^9 + 64

Ответы

Автор ответа: sebrithien
3

\displaystyle \tt x^3+8=x^3+2^3=(x+2)(x^2-2x+2^2)=\boxed{\bold{(x+2)(x^2-2x+4)}}

\displaystyle \tt 27+a^3=3^3+a^3=(3+a)(3^2-3a+a^2)=\boxed{\bold{(3+a)(9-3a+a^2)}}

\displaystyle \tt 1+m^6=(1+m^2)(1-1m^2+m^4)=\boxed{\bold{(1+m^2)(1-m^2+m^4)}}

\displaystyle \tt p^9+64=p^{3\cdot3}+4^3=(p^3)^3+4^3=(p^3+4)((p^3)^2-p^3\cdot4+4^2=\boxed{\bold{(p^3+4)(p^6-4p^3+16)}}

Автор ответа: artemlis2703
1

Ответ:

1.(x + 2)(x ^{2}  - 2x + 4)

2.(3 + a)(9 - 3a +  {a}^{2} )

3.(1 + m {}^{2} )(1 - m {}^{2}  + m {}^{4})

4.(p {}^{3}  + 4)(p {}^{6}  - 4 {p}^{3}  + 16)

Похожие вопросы